BI 2536 induces gasdermin E-dependent pyroptosis in ovarian cancer - Huo, Jianting; Shen, Yuhong; Zhang, Yuchen; Shen, Lifei (Frontiers in Oncology, 2022)
Background: The frequent emergence of drug resistance to chemotherapy is a major obstacle for the treatment of ovarian cancer. There is a need for novel drugs to fulfill this challenge. Pyroptosis-inducing drugs can inhibit tumor growth. However, their roles in ovarian cancer have not been demonstrated. Methods: We tested the effectiveness of a novel drug, BI 2536, which we found in colorectal cancer. Cell proliferation, cell cycle, and drug-induced apoptosis and pyroptosis were tested. In vivo treatments were performed using a cell-derived xenograft model. Results: BI 2536 significantly inhibited the proliferation of ovarian cancer cells and induced cell cycle arrest at the G2/M phases. After BI 2536 treatment, DNA fragmentation and PS exposure on the outside of apoptotic cells were detected. Moreover, the pyroptotic phenotype of ovarian cancer cells along with the release of LDH and HMGB1 were observed, indicating the leakage of cells. Western blot analysis verified that BI 2536 induced GSDME-mediated pyroptosis. Pyroptosis was abolished after additional treatment with Z-DEVD-FMK, a caspase-3 inhibitor. Thus, BI 2536 induced pyroptosis in ovarian cancer through the caspase-3/GSDME pathway. In vivo experiments further demonstrated the antitumoral effect and ability of BI 2536 to accumulate CD8+ T cells in ovarian cancer. Conclusion: In this study, we identified BI 2536 as an effective anti-ovarian cancer drug that inhibits proliferation, arrests the cell cycle, induces apoptosis and pyroptosis, and leads to the accumulation of CD8+ T cells in tumor sites. Drug-induced pyroptosis may have promising prospects for reducing side effects and activating immune responses.